ANALISIS LOYALITAS PASIEN DENGAN METODE STRUCTURAL EQUATION MODELING (SEM) DI RS NUR HIDAYAH - Chanif Kurniasari (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Nur Hidayah General Hospital is a private hospital that is professional in serving the public health needs. the sustainability of the hospital depends on the loyal patient. To create patient loyalty, hospitals need to have sustainable competitive advantage by establishing trust and good hospital image. The outpatient installation is due to a decrease in the number of patient visits. This study begins with the distribution of questionnaires, then descriptive statistical processing, and tests the linkages between service quality, satisfaction, trust, complaint, hospital image and loyalty of patients using Structural Equation Modeling (SEM).Objective: Knowing the analysis of loyalty patient in Nur Hidayah Hospital.Result: After data analysis using Structural Equation Model (SEM) obtained the results that the quality of service does not significantly affect the loyalty of patients in NurHidayah Hospital Yogyakarta. While the quality of service to patient satisfaction and patient satisfaction to patient loyalitas both have a significant effect.